2010
DOI: 10.1167/10.10.17
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spacing regularity on visual crowding

Abstract: Crowding limits peripheral visual discrimination and recognition: a target easily identified in isolation becomes impossible to recognize when surrounded by other stimuli, often called flankers. Most accounts of crowding predict less crowding when the target-flanker distance increases. On the other hand, the importance of perceptual organization and target-flanker coherence in crowding has recently received more attention. We investigated the effect of target-flanker spacing on crowding in multi-element stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 32 publications
6
51
1
Order By: Relevance
“…Our findings with peripheral vernier stimuli are very similar to previous findings with foveally presented verniers (Malania et al, 2007;Sayim et al, 2008Sayim et al, , 2010. Very similar effects of grouping were also found with Gabor stimuli (Saarela et al, 2009;Saarela et al, 2010) and letters (Saarela et al, 2010) presented in the periphery.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings with peripheral vernier stimuli are very similar to previous findings with foveally presented verniers (Malania et al, 2007;Sayim et al, 2008Sayim et al, , 2010. Very similar effects of grouping were also found with Gabor stimuli (Saarela et al, 2009;Saarela et al, 2010) and letters (Saarela et al, 2010) presented in the periphery.…”
Section: Discussionsupporting
confidence: 91%
“…So, when is bigger better in crowding? We proposed that crowding diminishes when the target ungroups and stands out from the flankers (Malania et al, 2007;Saarela et al, 2009;Saarela, Westheimer, & Herzog, 2010;Sayim, Westheimer, & Herzog, 2008;Sayim et al, 2010. Bigger is better in the short and long flanker conditions because adding flankers enhances flanker-flanker grouping and, thus, target ungrouping from the flankers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference most likely reflects differences in the number and arrangement of flankers in the three tasks. Indeed, many recent studies have found varied results when configurations or grouping of flankers and targets are manipulated within and across tasks (Danilova & Bondarko, 2007;Levi & Carney, 2009;Livne & Sagi, 2010;Saarela, Westheimer, & Herzog, 2010). Crowding zones are generally elongated, with the principal axis aligned with the center of the fovea.…”
Section: Is Crowding Task Independent?mentioning
confidence: 99%
“…These interpretations, however, have been challenged by recent flndings (Malania, Herzog, & Westheimer, 2007;Sareela, Westheimer, & Herzog, 2010;Sayim et al, 2008) suggesting the involvement of midlevel grouping processes. For example, Malania et al (2007) found that adding multiple flankers on either side of the target led to a reduction of the masking effect, contrary to predictions from lateral inhibition and pooling accounts.…”
mentioning
confidence: 99%